2016
DOI: 10.19044/esj.2016.v12n28p188
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Orientation, Business Development Services, Business Environment, and Performance: A Critical Literature Review

Abstract: The role of entrepreneurial orientation in firms has been a major area of interest to many scholars in the past. Entrepreneurially oriented firms are innovative, calculated risk-takers, and proactively reach markets ahead of their competitors. This paper examines the role of business development services, internal and external business environments on the relationship between entrepreneurial orientation and firm's performance. The article is a theoretical discourse and uses literature from secondary sources in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 10 publications
0
22
0
4
Order By: Relevance
“…Data were collected through mail questionnaires and the results indicated that there is a significant relationship between EO and the performance of SMEs. Okeyo, Gathungu & K'Obonyo [59] examined the association between EO, business development services, business environment and firm's performance. The findings also revealed that business development services play a mediating role in the EO and performance relationship and that external environment moderates this relationship.…”
Section: E Empirical Reviewmentioning
confidence: 99%
“…Data were collected through mail questionnaires and the results indicated that there is a significant relationship between EO and the performance of SMEs. Okeyo, Gathungu & K'Obonyo [59] examined the association between EO, business development services, business environment and firm's performance. The findings also revealed that business development services play a mediating role in the EO and performance relationship and that external environment moderates this relationship.…”
Section: E Empirical Reviewmentioning
confidence: 99%
“…Proactiveness is related to opportunity recognition or taking of initiative (Okeyo et al , 2016). According to Venkatraman (1989) it can be defined as looking for novel opportunities in the market and firms can be pro-active by foreseeing demands of future and new opportunities in the market, taking an interest in developing markets, shaping the environment, and launching new products and services ahead of their competitors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since it has, yet, been recommended that every dimensions of EO may not generally be favorable or advantageous for firm performance (Hughes and Morgan, 2007), value was added by expanding the understanding of the impacts of EO on SMEs performance, by also looking at the impact of each dimension on SMEs performance. The latest research (Okeyo et al , 2016) recommended using a contingency framework to focus on how other factors are likely to affect EO and performance relationship. Therefore, the study focused on EO specifically, and investigated the effects of EO as a whole and its dimensions on SMEs performance with mediating role of differentiation strategy and, using data collected from SMEs of Pakistan, contributes to filling this gap in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Innovativeness refers to a firm's behavior to generate new ideas leading to new or improved processes, products, or services (Rauch, et al, 2009). Innovativeness is also related to creativity which is a source of ideas that can lead to innovation of products, services, processes, markets or technology which leads to increased business performance (Okeyo, Gathungu, & K'Obonyo, 2016). Innovation can be measured in terms of new technology,products and markets (Giudici&Reinmoeller, 2013;Milovanovic&Wittine, 2014).…”
Section: Conceptual Frameworkmentioning
confidence: 99%